A new species of Heterogorgia Verrill, 1868 (Octocorallia, Malacalcyonacea) from a mesophotic fishing shoal in the eastern Pacific - Breedy, Odalisca; Murillo-Cruz, Catalina; Cortés, Jorge (Zootaxa, 2024)
Heterogorgia abdita sp. nov. is a newly identified mesophotic octocoral species collected at Tigre shoal off Santa Elena Peninsula (Pacific Costa Rica). The new species is described based on distinctive morphological characters that classify it within the genus Heterogorgia. It is characterised by its conspicuous small branching colony with prominent calyces and thin branches. While its scleroma aligns with the genus, the presence of club-like spindles is notable, as these have previously been observed only in the sole Atlantic Heterogorgia species. This study enhances our understanding of the intriguing genus Heterogorgia and contributes to the knowledge of octocoral biodiversity within the Área de Conservación Guanacaste north Pacific Costa Rica and the broader marine biodiversity of the eastern tropical Pacific.